Vicissitudes in teacher training in Bogotá (Praxis Educativa, 2015)
You may find the spot where some conceptualizations of teacher education are appreciated, as alluded to professionalization. Regarding training, may be noted that the policies of accreditation of university programs represent an attempt to improve teacher training future. In this sense one can observe evidence of sensing the intention not only to talk about the teaching profession but also noting those efforts made by shaping academic research groups to ensure the quality of teacher training; same purpose research groups in the educational field within them appear analyzes relating to the service of teaching are performed and conducted educational research that seeks to recognize the competence of teachers and their knowledge about their practice.
Keywords: teacher training; professionalism; quality of education